ANALISIS RASIO MODAL KERJA PADA PT. HM SAMPOERNA TBK - Anggelina Manengkey; Frendy A. O Pelleng; Dantje Keles (JURNAL ADMINISTRASI BISNIS, 2017)
Working capital is very important for any company, because almost allcompanies need working capital to finance the day-to-day operations of thecompany. Companies must be able to manage working capital well so thatoperational activities can run smoothly and can achieve the optimal profit asexpected by the company. This study aims to analyze and know how theworking capital adequacy ratio. This research was conducted at PT. HMSampoerna Tbk. According to Sutrisno (2009), "Working capital is one ofthe elements of assets that are very important in the company becausewithout working capital the company cannot fill the necessity to run theactivities". The method used in this study is descriptive quantitative andanalysis tool used is Working Capital Adequacy Ratio which consists of threetypes of ratios are the ratio of Total Assets to Net Working Capital, CurrentLiabilities to Net Working Capital and Working Capital Turnover. The dataused are secondary data from financial statements namely balance sheet andincome statement from PT. HM Sampoerna Tbk. The results of the studyexplain that the calculation of the ratio of Total Assets to Net WorkingCapital in 2013 to 2016 is quite good. While the calculation of CurrentLiabilities to Net Working Capital Ratio in 2013 and 2014 is quite good, butthe calculation results in 2015 and 2016 decreased to 0.17 and 0.23. And thecalculation results Working Capital Turnover in 2014 increased, but thendeclined in 2015 and 2016, indicating liquidity on this ratio more effective.Overall working capital at PT HM Sampoerna Tbk has good working capitalmanagement. The results of the working capital adequacy ratio analysis willgive an idea of how the company can manage its working capital. Liquiditylevel at PT. HM Sampoerna Tbk is quite good. This indicates that theadequacy of working capital at PT. HM Sampoerna Tbk is quite stable. Werecommend PT. HM Sampoerna Tbk can use and allocate working capitaloptimally. So the company can cover its short-term liabilities in order for thecompany to generate profit in each period.Keywords: Working Capital, Net Working Capital, Working Capital Ratio